(untitled) (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2026)
This study investigates the effectiveness of expression-based activities in developing English speaking skills among students in underperforming schools of Narpay district. Rural learners often face challenges such as limited fluency, weak discourse organization, and speaking anxiety due to traditional grammar-focused instruction and lack of authentic language exposure. Structured activities using formulaic expressions, discourse markers, and functional conversational routines were implemented to improve communicative competence. Pre- and post-speaking assessments, classroom observations, and student feedback indicated significant improvement in fluency, coherence, and interactional competence. The study concludes that integrating expression-based activities into English lessons is an effective and sustainable strategy for enhancing speaking competence in rural EFL contexts